Tension Pneumocephalus Following Orbital Exenteration. Issue 1 (January 2016) - Shieh, Wen-Shi; Farrell, Christopher; Curry, Joseph; Murchison, Ann P.; Bilyk, Jurij R.
Abstract : Pneumocephalus is a known complication of skull base surgery, but is rarely seen by orbital surgeons. We report a case of postoperative mental status changes after exenteration due to tension pneumocephalus. After surgical and medical management, the patient's pneumocephalus resolved and she recovered fully. Risk factors for tension pneumocephalus, mechanism, clinical presentation, and management techniques are discussed.